EXTRA-ARTICULAR MANIFESTATIONS ASSOCIATED WITH HLA-B27 IN PEDIATRIC PATIENTS, INCLUDING UVEITIS, INFLAMMATORY BOWEL DISEASE AND DERMATOLOGICAL INVOLVEMENT: A SYSTEMATIC REVIEW - Zuzanna Przybylska; Bartłomiej Przystaś; Sebastian Podeszwa; Wiktor Rolski; Mikołaj Piotr Hobot; Paweł Michalski; Aleksandra Anna Purpura; Paulina Michalska; Magdalena Grzechowiak; Gabriela Patrycja Dobosz (International Journal of Innovative Technologies in Social Science, 2026)
Background: HLA-B27 is strongly associated with spondyloarthritis and related conditions. While extra-articular manifestations (EAMs) are well characterized in adults, their prevalence and clinical relevance in pediatric populations remain less clearly defined.Aim: To systematically review and quantitatively synthesize evidence on the association between HLA-B27 positivity and extra-articular manifestations, including uveitis, inflammatory bowel disease (IBD), and dermatological involvement, in pediatric patients.Material and methods: A systematic literature search of PubMed, Embase, Scopus, and Google Scholar was performed. Observational studies reporting extra-articular manifestations in HLA-B27–positive pediatric patients were included.Results: Twenty-five studies met the inclusion criteria and were included in the qualitative synthesis. Uveitis was the most frequently reported manifestation, with consistently higher occurrence in HLA-B27–positive pediatric patients across cohorts. Inflammatory bowel disease and dermatological manifestations were reported less frequently but remained consistent components of the disease spectrum.Conclusions: HLA-B27 positivity in pediatric patients is associated with a significant burden of extra-articular disease. Early recognition and multidisciplinary management may improve long-term outcomes. Integration of digital health tools and improved healthcare system strategies may play a key role in optimizing early detection and management.